Simulation of material requirements planning system According to FOQ, EOQ, L4L A study in the General Company for woolen industries / blankets factory - خلف, بتول عطية (Journal of Economics and Administrative Sciences, 2009)
This paper is submitted as anew approach to simulate manufacturing control & planning system to define the problem of designing control system on the needs for materials.Production planning & control is a total and complex operation, resides in the essence of manufacturing companies operations. The successful process of production planning and control systems is critical for the staying of manufacturing organizations in markets leading to the increasing consumer competition and which dominate most of manufacturing sectors because of the market oriented economy , thus , what has happened previously , that the companies possessed a great inventory of crude material, components, and groupings and they use in flexible techniques for production planning, depend on controlling , the stored and the long –term prediction.Today , companies find that the operations must be more dynamic granting the customer choices because of products redundancy with the reducing of products life cycle .All this has a great effect on the method of designing the production means with the big changes in manufacturing system in technological applying based on computer on all company levels.This paper reviews some of changes in the fields of the systems of production and scheduling planning and control. This paper in particular aims at applying high computer techniques like discontinuous events simulation systems to schedule production .The production scheduling in its broad sense pass on all production planning and control levels as from predicting future selling's volume and market demand the main production scheduling to the planning of needs for materials , thus , the paper depends on using simulation by the assistance of EXCEL program through its applying on three methods to plan the needs for the blanket products and extrapolating the random numbers for one year , and depending on the extrapolated costs , it was obvious that the best methods are the method of equivalent batch volume (L4L) , the method of constant demand (FOQ) AND THE Economic batch volume to define the batch volume through the quantities and their achievement times.